Effects of Processing Difficulty on Eye Movements in Reading: A Review of Behavioral and Neural Observations - Shun-nan Yang (Bern Open Publishing, 2012)
In reading, text difficulties increase the duration of eye fixation and the frequency of refixation and regression. The present article reviews previous attempts to quantify these effects based on the frequency of effect theory (FET), and links these effects to results from microstimulation of primate supple-mentary eye fields. Observed stimulation effects on the latency and frequency of visually-guided saccades depend on the onset time of electric current relative to target onset, and the strength of applied current. Resultant saccade delay was only observed for those made towards a highly predictive location ipsilateral to stimulated SEF sites. These findings are inter-preted in the context of reading, where the detection of processing difficulty allows a suppression signal to supersede a forward saccade signal in a time race. This in turn permits a cognitively-based refixation/regression to be initiated in place of the suppressed forward saccade.